2007
DOI: 10.1371/journal.pone.0001350
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of a Measurement Tool to Assess Systematic Reviews (AMSTAR)

Abstract: BackgroundThousands of systematic reviews have been conducted in all areas of health care. However, the methodological quality of these reviews is variable and should routinely be appraised. AMSTAR is a measurement tool to assess systematic reviews.MethodologyAMSTAR was used to appraise 42 reviews focusing on therapies to treat gastro-esophageal reflux disease, peptic ulcer disease, and other acid-related diseases. Two assessors applied the AMSTAR to each review. Two other assessors, plus a clinician and/or me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
344
1
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(360 citation statements)
references
References 63 publications
4
344
1
11
Order By: Relevance
“…The present study was not intended to perform a quality appraisal of the published systematic reviews, but future studies using AMSTAR-a quality measurement instrument 117 or its revised version-R-AMSTAR 118 could be performed to evaluate the systematic reviews in palliative care. These two tools have established reliability and validity 119,120 and previous such reports using AMSTAR tool were published in Indian medical journals. 121 More than one half of hospice and palliative care studies were reported in just 43 journals which were not specialist palliative and hospice care journals.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was not intended to perform a quality appraisal of the published systematic reviews, but future studies using AMSTAR-a quality measurement instrument 117 or its revised version-R-AMSTAR 118 could be performed to evaluate the systematic reviews in palliative care. These two tools have established reliability and validity 119,120 and previous such reports using AMSTAR tool were published in Indian medical journals. 121 More than one half of hospice and palliative care studies were reported in just 43 journals which were not specialist palliative and hospice care journals.…”
Section: Discussionmentioning
confidence: 99%
“…The quality (based on the risk of bias) of each study was categorized as "good," "fair," or "poor" using the U.S. Preventive Services Task Force criteria for randomized trials and cohort studies (33), Quality Assessment of Diagnostic Accuracy Studies-2 for diagnostic accuracy studies (34), and Assessment of Multiple Systematic Reviews for systematic reviews (35). The strength of overall evidence was graded as high, moderate, low, or very low using methods based on quality of evidence, consistency, directness, precision, and reporting bias.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Eligible quantitative SRs were critically appraised using the AMSTAR tool (http://amstar.ca/), an 11-item tool with well-established validity and reliability that is extensively used to evaluate quantitative SRs. [20][21][22] Critical appraisal of qualitative studies is an area of ongoing debate, and currently there is no consensus on an appropriate critical appraisal tool for qualitative research, and researchers are advised to choose a tool specific to this research paradigm. 23 Therefore, eligible qualitative SRs were critically appraised using five criteria designed to evaluate the rigor of qualitative reviews.…”
Section: Quality Appraisalmentioning
confidence: 99%